DETERMINAN TINDAK PIDANA KORUPSI PENYALAHGUNAAN WEWENANG YANG DILAKUKAN OLEH PEJABAT PUBLIK - Bagaskoro, M. Rizal; Khumaeroh, Irda Nur (LPPM STIH Awang Long, 2024)
Article 3 of Law No. 31 of 1999 jo. Law No. 20 of 2001 on the Eradication of Corruption (hereinafter referred to as the Corruption Eradication Law) defines abuse of authority as when an individual or group benefits themselves, others, or a corporation by misusing the authority, opportunities, or resources available to them due to their position, resulting in harm to state finances or the national economy. This writing aims to understand and analyze the determinants of abuse of authority by public officials according to the Corruption Eradication Law and corruption offenses related to abuse of authority by public officials from a governmental administrative perspective. The type of research in this writing is normative juridical, which emphasizes document studies or library research. The discussion in this writing includes: The determinants of abuse of authority by public officials according to the Corruption Eradication Law, which consist of internal factors that drive corruption from within and external factors that trigger corrupt behavior from outside the perpetrator. Corruption offenses related to abuse of authority by public officials in a governmental administrative perspective, juridically, abuse of authority in the Administrative Law is declared to occur when a government body and/or official makes decisions and/or takes actions beyond their authority, mixes authorities, and/or acts arbitrarily.